KOMPETENSI GURU BAHASA ARAB DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA BELAJAR - Achmad, Andi; Hikmah, Khizanatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the competence of Arabic language teachers in implementing the Merdeka Curriculum at MA Dafi Pesantren Al-Qur'an Science Sidoarjo and the challenges faced. This research uses descriptive qualitative methods, data collected through observation, interviews, and documentation. The results showed that teachers have good competence in understanding student characteristics, designing project-based learning, and applying interactive methods and varied evaluations. However, the implementation of Merdeka Curriculum faces obstacles such as low student motivation, limited interesting teaching materials, lack of supporting environment for Arabic language practice, and minimal utilization of technology in learning. This study recommends strengthening teacher training in technology integration, developing teaching materials that are more contextual and applicable, and institutional support in creating a more effective learning environment. The results of this study are expected to be a reference for improving Arabic learning strategies in the Merdeka Curriculum in the pesantren environment.